2020
DOI: 10.1177/2325967120969151
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sport After Arthroscopic Treatment of Posterior Shoulder Instability

Abstract: Background: Arthroscopic treatment of posterior shoulder instability has become more popular and effective in recent years, but few data are available concerning the rate of return to sport. Purpose: To present our experiences with arthroscopic posterior labral reconstruction in athletes and review our results, with a particular focus on the rate of return to sport. Study Design: Case series; Level of evidence, 4. Methods: Included in the study were 40 arthroscopic stabilizations performed because of posterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…16,26 Arthroscopic capsulolabral repair for posterior shoulder instability has been shown to improve pain and stability, with .90% of patients capable of returning to sport at short-term to midterm follow-up. 10,19 However, despite arthroscopic stabilization, in certain populations, only two-thirds of patients return to sport (RTS) at the same preinjury level, and up to one-third experience persistent pain and/or instability, necessitating revision surgery. 12 Furthermore, long-term outcomes (ie, .10 years) after arthroscopic capsulolabral repair for posterior shoulder instability have not yet been reported.…”
mentioning
confidence: 99%
“…16,26 Arthroscopic capsulolabral repair for posterior shoulder instability has been shown to improve pain and stability, with .90% of patients capable of returning to sport at short-term to midterm follow-up. 10,19 However, despite arthroscopic stabilization, in certain populations, only two-thirds of patients return to sport (RTS) at the same preinjury level, and up to one-third experience persistent pain and/or instability, necessitating revision surgery. 12 Furthermore, long-term outcomes (ie, .10 years) after arthroscopic capsulolabral repair for posterior shoulder instability have not yet been reported.…”
mentioning
confidence: 99%
“…between 70% and 95%. [31][32][33][34][35][36][37][38][39][40][41][42][43] However, the estimates of the rate of return to preinjury levels of activity and competition are currently limited, potentially due to a lack of activity-level assessment standardization. 22,30,37 A recent meta-analysis identifying studies reporting RTS after surgery for shoulder instability found that, on average, 73% of people returned to any sport and 65% returned to their preinjury level of sport.…”
mentioning
confidence: 99%
“…41 Factors currently known to influence RTS include age, sex, surgical technique, traumatic injury pattern, contact and collision sports, and overhead sports participation. 18,21,35,49,56 RTS after shoulder surgery is of paramount importance to both athletes and their treating physicians. Despite the numerous advances in the treatment of shoulder instability, recent studies have begun to identify discrepancies between objective functional data and patient perceptions of their injury and readiness to RTS.…”
mentioning
confidence: 99%
See 2 more Smart Citations